A justa e prévia indenização na desapropriação - Nakamura, André Luiz dos Santos (2012)
The right to property, its original configuration, selfish and individualistic, evolved into the social function of property. Currently, the social function is a decisive factor in defining the limitations and restrictions on property rights and its consequent compensation. The expropriation, guarantees of property rights, too, has gone through transformations. The just compensation should be seen not only from the side of the dispossessed. The expropriating is also protected by the guarantee of just compensation. Sealing the illicit enrichment is the decisive criterion for the determination of just compensation. The extension of protection to property rights and compensation for expropriation should be established individually, considering the use of the property, in particular, the fulfillment of its social function